Letter - Peterborough & District Trades and Labour Council, 7 May 1926 (page 2)
1926-05-07 "Letter - Peterborough & District Trades and Labour Council, 7 May 1926 (page 2)" [g0357002.jpg], 7 May 1926, Peterborough & District Trades and Labour Council